(untitled) (INNOVATIVE ECONOMY, 2023)
Balaniuk I.F., Ivanochko B.R. MEASURES FOR ATTRACTING INVESTMENTS IN BUSINESS DEVELOPMENT OF TERRITORIAL COMMUNITIES ON THE BASIS OF MARKETING STRATEGY Purpose. The aim of the article is determination and substantiation of measures to attract investment in business development of territorial communities based on marketing strategy, as well as establishing the relationship between investment potential and the attractiveness of communities. Methodology of research. The methodological basis of the study is the scientific works of domestic scientists on the issues of economic development of territorial communities, attraction of investments in communities, state management of investments, formation of strategic development plans. General scientific and specific methods were used to achieve the goal, such as: dialectical method of scientific knowledge – to consider the essence of attracting investments to territorial communities; analysis and synthesis – to clarify the relationships between subjects of investment activity in communities; graphic – for a visual representation of the proposed activities; abstract and logical – for the formation of research conclusions and proposals. Findings. Measures to attract external investments in the economic development of territorial communities have been analysed. It was established that at the stage of strategic planning, a comprehensive analysis of the community’s available resources is necessary. It has been suggested to evaluate the investment potential using a SWOT analysis. The essence of the marketing strategy for improving the investment attractiveness of communities is revealed. The need to create a community investment activity commission as the main centre for making management decisions regarding the development and implementation of organizational and economic measures to attract investments has been substantiated. Originality. It has been is proposed to consider measures to attract investments in development of territorial communities as joint activities of local self-government bodies, business and the public to create conditions for development in the community, improve the general investment attractiveness, and form programs of social and economic development. Practical value. Developed proposals for improving the investment potential of territorial communities based on a marketing strategy can be used by local self-government bodies in planning social and economic development. Key words: investments, territorial communities, social and economic development, marketing strategy, business development, potential, attractiveness.